Measurement of the WW and WZ production cross section using final states with a charged lepton and heavy-flavor jets in the full CDF Run II data set - Aaltonen, T.; Amerio, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
We present a measurement of the total WW and WZ production cross sections in pp collision at s=1.96 TeV, in a final state consistent with leptonic W boson decay and jets originating from heavy-flavor quarks from either a W or a Z boson decay. This analysis uses the full data set collected with the CDF II detector during Run II of the Tevatron collider, corresponding to an integrated luminosity of 9.4 fb-1. An analysis of the dijet mass spectrum provides 3.7? evidence of the summed production processes of either WW or WZ bosons with a measured total cross section of ?WW+WZ=13.7±3.9 pb. Independent measurements of the WW and WZ production cross sections are allowed by the different heavy-flavor decay patterns of the W and Z bosons and by the analysis of secondary-decay vertices reconstructed within heavy-flavor jets. The productions of WW and of WZ dibosons are independently seen with significances of 2.9? and 2.1?, respectively, with total cross sections of ?WW=9.4±4.2 pb and ?WZ=3.7-2.2+2.5 pb. The measurements are consistent with standard-model predictions. © 2016 American Physical Society.
Citation: Aaltonen, T., Amerio, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Zucchelli, S. (2016). Measurement of the WW and WZ production cross section using final states with a charged lepton and heavy-flavor jets in the full CDF Run II data set. Physical Review D - Particles, Fields, Gravitation and Cosmology, 94(3). doi:10.1103/PhysRevD.94.032008